Application of the Open Data Kit for Data Collection Presence of Primary School Teachers - Purbasari, Ayi; Gusdya, Wanda; Mulyanto, Ferry; Nurlatifah, Vina Fitria (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2021)
The Open Data Kit (ODK) originated as a google.org initiative where research efforts were focused on applying technology to assist developing countries in the health and environment sectors. ODK is an open-source tool that helps organizations, writers / researchers, field workers, and manage mobile data collection solutions. Its goal is to create open-source and standards-based tools that are easy to try, easy to use, easy to modify and easy to measure. This research was conducted to help teachers and Korwil Operators to collect and manage teacher attendance data at each elementary school in Ciater sub-district by utilizing the Open Data Kit as a medium for collecting and managing primary school teacher attendance data. This research was conducted by conducting literature studies, interviews and observations, and studying the use of the Open Data Kit. Furthermore, the stages will be carried out to define the needs of analysis, design and implementation. The final result of this research is a presence data collection application that utilizes the Open Data Kit as a medium consisting of ODK Collect as a data collection tool and ODK Aggregate as a tool for managing data.